2012
DOI: 10.1177/0894845312468060
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Validity of the Emotional and Personality-Related Career Decision-Making Difficulties Questionnaire in Turkish Culture

Abstract: The goal of this study was to examine the emotional and personality-related career decision-making difficulties of high school students in Turkish culture, using the model proposed by Saka and Gati. A sample of 523 high school students filled out the Turkish version of the Emotional and Personality-Related Aspects of Career Decision-Making Difficulties (EPCD) questionnaire. Cluster and confirmatory factor analyses supported the ternary classification system of the emotional and personality-related career decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
2
16
1
Order By: Relevance
“…Structural validity of the EPCD . The structural validity of the EPCD has been tested cross‐culturally, and there has been convergent evidence supporting the three‐factor structure (Hou et al, 2015; Jin et al, 2015; Oztemel, 2013; Saka & Gati, 2007; Saka et al, 2008). Although research showed that two or three items loaded on the self‐concept and identity domains of the EPCD might not apply to an East Asian context, the general taxonomy system of the EPCD still held after deleting those items (Hou et al, 2015; Jin et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Structural validity of the EPCD . The structural validity of the EPCD has been tested cross‐culturally, and there has been convergent evidence supporting the three‐factor structure (Hou et al, 2015; Jin et al, 2015; Oztemel, 2013; Saka & Gati, 2007; Saka et al, 2008). Although research showed that two or three items loaded on the self‐concept and identity domains of the EPCD might not apply to an East Asian context, the general taxonomy system of the EPCD still held after deleting those items (Hou et al, 2015; Jin et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…For example, it was found that the EPCD was associated with emotional and personality‐related variables, career decision‐making self‐efficacy, and the CDS (Hou et al, 2015; Jin et al, 2015; Saka & Gati, 2007). It was also found that the EPCD showed differential scores for students with different help‐seeking intentions, decidedness, and self‐reported difficulties (Gati, Asulin‐Peretz, & Fisher, 2012; Oztemel, 2013; Saka & Gati, 2007). Longitudinally, the EPCD was found to successfully predict later decidedness and choice confidence (Gati et al, 2012; Saka et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structural validity of EPCD was also generally supported, although the uncrystallized identity difficulty category was located empirically under the self-concept and identity cluster in the Israeli sample in accordance with the theoretical model but was categorized into the anxiety cluster in the American sample. In another study, Oztemel (2013) tested the structure of EPCD with a sample of Turkish high school students. The exploratory cluster analysis showed a similar structure of EPCD-Turkish version with the hypothesized theoretical model by Saka et al (2008) with one difference: The difficulty category ''anxiety about the outcomes'' was included in the self-concept and identity instead of anxiety cluster.…”
Section: Review Of Career Decision-making Assessmentmentioning
confidence: 99%